2020
DOI: 10.1186/s12864-020-6675-0
|View full text |Cite
|
Sign up to set email alerts
|

microRNA profiling in the Weddell seal suggests novel regulatory mechanisms contributing to diving adaptation

Abstract: Background: The Weddell Seal (Leptonychotes weddelli) represents a remarkable example of adaptation to diving among marine mammals. This species is capable of diving > 900 m deep and remaining underwater for more than 60 min. A number of key physiological specializations have been identified, including the low levels of aerobic, lipid-based metabolism under hypoxia, significant increase in oxygen storage in blood and muscle; high blood volume and extreme cardiovascular control. These adaptations have been link… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 90 publications
2
8
0
Order By: Relevance
“…Using Basic Local Alignment Search Tool, we identified these seal proteins and mapped them to gene families containing 60S ribosomal proteins, cytokines, calcium-binding proteins, histones, and ubiquitin proteasome (Supplementary Table 3 ). The high rate of protein-coding gene family expansions in the Weddell seal is consistent with a previous analysis of microRNA family size showing high rates of gain and loss in the Weddell seal lineage versus dog 38 .
Fig.
…”
Section: Resultssupporting
confidence: 89%
“…Using Basic Local Alignment Search Tool, we identified these seal proteins and mapped them to gene families containing 60S ribosomal proteins, cytokines, calcium-binding proteins, histones, and ubiquitin proteasome (Supplementary Table 3 ). The high rate of protein-coding gene family expansions in the Weddell seal is consistent with a previous analysis of microRNA family size showing high rates of gain and loss in the Weddell seal lineage versus dog 38 .
Fig.
…”
Section: Resultssupporting
confidence: 89%
“…In Steller sea lions ( Eumetopias jubatus ), mass-specific total body oxygen stores not only increase with age, but shift predominantly to muscle for primary oxygen storage ( Richmond et al, 2006 ). Similar age-related changes in oxygen-storing capacity have been observed in other pinniped species, such as the Weddell seal ( Leptonychotes weddellii ) ( Penso-Dolfin et al, 2020 ). Expression and activity of antioxidant enzymes were also found to increase with maturation in hooded seals ( Cystophora cristata ) and ringed seals ( Pusa hispida ) ( Elsner et al, 1998 ; Vázquez-Medina et al, 2006 , 2011b ).…”
Section: Introductionsupporting
confidence: 70%
“…Another research demonstrated that during hypoxic events, the upregulation of miR-24, which inhibits apoptosis, combined with the downregulation of miR-210, an indirect stabilizer of HIF1, could potentially promote neuronal preservation and trigger an adaptive hypoxic response in naked mole rats ( Logan et al 2020 ). In the case of aquatic mammals, Penso-Dolfin et al (2020 ) investigated the role of miRNAs in the adaptive evolution of diving capacities in Weddell seals ( Leptonychotes weddelli ). Through differential expression analysis, they identified potential protective mechanisms in individual tissues, particularly relevant to hypoxia tolerance and anti-apoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%